Ketimpangan Antardaerah, Desentralisasi dan Eksistensi Korupsi di Indonesia - Sukadana, I Wayan (Jurnal Ekonomi dan Pembangunan Indonesia, 2009)
Decentralization has been implemented for eight years. However, corruption has not been lessened yet within the decentralization era. Bad regulations and investment climate are suspected to be a cause of the situations. Good regulation and investment climate appear if the interjurisdictional competitions exist. The incentive for competition is the equality of economic endowment among regions, or each region has their own tradeable "technology" that comparable to others. Inequality in "technology" implies that the region with rich "technology" is more attractive eventhough there are bad regulation and the investment climate. In contrary, in region with less "technology", corruption will appear because of weak control of the society to the bureaucracy. The strong assumption of this paper is short memories of voters. This paper attempts to estimate and to model the relation between economic variable and corruption. The estimation uses the cross section data among kabupaten/kota in Indonesia in 2004. The estimation shows that economic endowment variable positively and significant correlated to the investment level. On the other hand, the effect of corruption is statistically insignificant in explaining the investment level. The subsequent part of this paper attempts to estimate and to model how the heterogeneity or inequality in "technology" affects the existence of corruption in Indonesia. The OLS regression of heterogeneity of domestic product (PDRB) against corruption index shows that the heterogeneity positively correlated with corruption level.